1987
DOI: 10.1111/j.1439-0523.1987.tb01170.x
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Anther Culture in a Genetically Wide Material of Winter Wheat (Triticum aestivum L.)

Abstract: In a screening experiment with 215 different winter cukivars of Triticum aestivum L. for response in anther culture, pollen embryos or callus were obtained from 200 different cukivars and green plants from 93 different cultivars. On average, from the whole material, 1.3 green plants were obtained per 100 anthers cultured. Variance components estimated from replicates with selected parts of the plant material indicated that for the formation of pollen embryos from anthers, interactions between genotypes and rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 4 publications
7
31
1
Order By: Relevance
“…useful for genetic analysis, particularly for mapping of quantitative traits El Attari et al, 1998;Caranta et al, 1997;Mahmood et al, 2003). Anther culture response is known to be under a strong genotypic influence (Rakoczy-Trojanowska et al, 1997;Reddy et al, 1985;Andersen et al, 1987;Petolino & Jones, 1986). Thus, when DH lines are produced, some cross combinations show a low efficiency in anther culture and some show segregation distortion in their DH lines.…”
Section: Mapping Populationsmentioning
confidence: 96%
“…useful for genetic analysis, particularly for mapping of quantitative traits El Attari et al, 1998;Caranta et al, 1997;Mahmood et al, 2003). Anther culture response is known to be under a strong genotypic influence (Rakoczy-Trojanowska et al, 1997;Reddy et al, 1985;Andersen et al, 1987;Petolino & Jones, 1986). Thus, when DH lines are produced, some cross combinations show a low efficiency in anther culture and some show segregation distortion in their DH lines.…”
Section: Mapping Populationsmentioning
confidence: 96%
“…Genotypic differences in androgenesis induction do exist (Anderson et al 1987;Tuvesson et al 1989). Some genotypes naturally react better than others in response to environmental changes, such as stress treatments applied to microspores.…”
Section: Introductionmentioning
confidence: 97%
“…Most of the studies on the inheritance of anther culture response in wheat have focused only on nuclear genetic control and have not examined the reciprocal effects (Becraft and Taylor 1992, Deaton et al 1987, Agache et al 1989, Moinei et al 1997. Tuvesson et al (1989) andChaudhery et al (2003) reported that maternal and cytoplasmic effects are not important for anther culture response.…”
mentioning
confidence: 96%